Pengaruh ROA, EPS dan DER Terhadap Harga Saham Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia: Penelitian - Nadila Berlian Pertiwi; Dade Nurdiniah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The purpose of this study was to analyze the effect of Return on Assets (ROA), Earning per Share (EPS), and Debt to Equity Ratio (DER) on the stock prices of banking companies listed on the Indonesia Stock Exchange (IDX) in the period 2020-2024. There are 47 banking companies listed on the Indonesia Stock Exchange on the IDX. The technique in this study used the Purposive sampling method which was used as sample selection, with criteria that produced 20 samples. Data analysis used the classical assumption test and panel data regression test including the t-test and F-test with the help of the E-views13 application. Based on the background, this study is based on the importance of stock prices as an indicator of company value and investment attractiveness, as well as the high fluctuations in stock prices influenced by the company's financial performance. From this study, several data can be obtained that partially ROA and EPS have a significant effect on stock prices, while DER does not have a significant effect. Simultaneously, the three independent variables have a significant effect on stock prices. This finding shows that the profitability of banking companies is a major concern for investors in making investment decisions in the capital market.